The impact of C-reactive protein testing on treatmentseeking behavior and patients' attitudes toward their care in Myanmar and Thailand - Rachel C. Greer; Thomas Althaus; Sabine Dittrich; Christopher C. Butler; Phaik Yeong Cheah; Tri Wangrangsimakul; Frank M. Smithuis; Nicolas P.J. Day; Yoel Lubell (PAGEPress Publications, 2023)
C-reactive protein (CRP) point-of-care testing can reduce antibiotic prescribing in primary care patients with febrile and respiratory illness, yet little is known about its effects on treatment-seeking behavior. If patients go on to source antibiotics elsewhere, the impact of CRP testing will be limited. A randomized controlled trial assessed the impact of CRP testing on antibiotic prescriptions in Myanmar and Thai primary care patients with a febrile illness. Here we report patients' treatmentseeking behavior before and during the twoweek study period. Self-reported antibiotic use is compared against urine antibacterial activity. Patients' opinions towards CRP testing were evaluated. Antibiotic use before study enrolment was reported by 5.4% while antimicrobial activity was detected in 20.8% of samples tested. During the study period, 14.8% of the patients sought additional healthcare, and 4.3% sourced their own antibiotics. Neither were affected by CRP testing. Overall, patients' satisfaction with their care and CRP testing was high. CRP testing did not affect patients' treatment-seeking behavior during the study period whilst modestly reducing antibiotic prescriptions. CRP testing appears to be acceptable to patients and their caregivers.